Cockpit as a source of piloting errors - A. L. Rybalkina (Научный вестник МГТУ ГА)
The article analyzes the various problems associated with the construction of a cockpit, which can contribute to piloting errors (relative positioning and various dials, perception of warning signals, features of spatial orientation). It is shown how the application of ergonomic principles can reduce the probability of error when working in the cockpit.